Predictive Power of f99 Repolarization Index for the Occurrence of Ventricular Arrhythmias. Issue 2 (25th November 2015) - Giuliani, Corrado; Swenne, Cees A.; Man, Sumche; Agostinelli, Angela; Fioretti, Sandro; Di Nardo, Francesco; Burattini, Laura
Abstract : Background: Defects of cardiac repolarization, noninvasively identifiable by analyzing the electrocardiographic (ECG) ST segment and T wave, are among the major causes of sudden cardiac death. Still, no repolarization‐based index has so far shown sufficient sensitivity and specificity to justify preventive treatments. Thus, the aim of this work was to evaluate the predictive power of our recently proposed f99 index for the occurrence of ventricular arrhythmias. Methods: Our study populations included 170 patients with implanted cardiac defibrillator (ICD), 44 of which developed ventricular tachycardia and/or fibrillation during the 4‐year follow‐up (ICD_Cases) and 126 did not (ICD_Controls). The f99 index, defined as the frequency at which the repolarization normalized cumulative energy reaches 99%, was computed in each of the 15 (I to III, aVl, aVr, aVf, V1 –V6, X, Y, Z) available ECG leads independently, and then maximized over the 6 precordial leads (f99_MaxV1 –V6 ), 12 standard leads (f99_Max12STD) and three orthogonal leads (f99_MaxXYZ) to avoid dispersion‐related issues. Each index predictive power was quantified as the area under the receiving operating characteristic curve (AUC). Results: Median f99_MaxV1 –V6, f99_Max12STD and f99_MaxXYZ values were significantly higher in the ICD_Cases than in the ICD_Controls (48 Hz vs. 35 Hz, P<0.05; 51 Hz vs. 43 Hz, P<0.05; 45 Hz vs. 31 Hz, P<10 −3 ; respectively), indicating a more fragmented repolarization in the former group. The AUC values were 0.62, 0.63 and 0.68, respectively. Conclusions: The f99 represents a promising risk index for the occurrence of ventricular arrhythmias, especially when maximized over the three orthogonal leads.